Advances in Applied Macroeconomics International Conference on Applied Economics (ICOAE) 2024, Belgrade, Republic of Serbia, July 11-13, Vol 2 - Tsounis, Nicholas; Vlachvei, Aspasia (Springer Proceedings in Business and Economics, 2025)
XIV, 550 p. 105 illus., 91 illus. in color.